Micellar and Interfacial Behavior of Mixed Systems Containing Glycoside‐Based Surfactant and Cationic Didecyldimethylammonium Chloride. Issue 5 (7th June 2015) - Han, Zhiguo; Yang, Xiuquan; Liu, Yong
Abstract: The behavior of binary mixtures of glycoside‐based surfactants in combination with didecyldimethylammonium chloride (DDAC) has been studied using surface tension measurements. The three glycoside‐based surfactants are nonionic decyl glycoside (APG), nonionic dodecyl ethoxy glycoside (AEG) and anionic disodium dodecyl ethoxy glycoside citrate (AEG‐EC). Lower critical micelle concentrations (CMC) and minimum molecular area ( A min ) values were obtained for all the mixed systems. The p C20 values of APG/DDAC and AEG‐EC/DDAC mixtures are larger than pure surfactants, while the values of AEG/DDAC are between those of AEG and DDAC. Interactions between the monomers have also been investigated by determining the interaction parameters. Negative β m and β s values indicate synergistic effects in both the mixed micelle and monolayer formation. For different mixed systems, interaction in the mixed micelle formation becomes stronger in the order: AEG/DDAC < AEG‐EC/DDAC < APG/DDAC. The degree of synergism in the mixed monolayer formation follows the order: AEG/DDAC < APG/DDAC < AEG‐EC/DDAC.